2019
DOI: 10.1002/arch.21637
|View full text |Cite
|
Sign up to set email alerts
|

Larval development and proteolytic activity of Anticarsia gemmatalis Hübner (Lepidoptera: Noctuidae) exposed to different soybean protease inhibitors

Abstract: Anticarsia gemmatalis represents a relevant factor for lowering soybean and other legume crop productivities.Protease inhibitors affect protein degradation and reduce the availability of amino acids, impairing the development and survival of insect pests. To evaluate the possible use of proteinaceous protease inhibitors in the management of this pest, the activities of midgut proteases and the growth and development of A. gemmatalis larvae exposed to soybean Bowman-Birk trypsin-chymotrypsin inhibitor (SBBI) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…This study also indicated a developmental component in physiological adaptations of P. brassicae larvae to short-term host plant switches, with fourth instars showing most adaptable feeding behaviors and highest gut protease activities on all diets tested (S1 Fig) . Similar results have been reported from several Lepidoptera where digestion of ingested plant tissues in the gut improves with larval age and is most versatile in actively feeding penultimate instars preceding pupation [34,[67][68][69]. Results from these reciprocal host plant switch experiments also implied that the length of time spent by larvae feeding on a diet was important to identify proteases that participate in rapid adaptation to dietary shifts.…”
Section: Plos Onesupporting
confidence: 79%
“…This study also indicated a developmental component in physiological adaptations of P. brassicae larvae to short-term host plant switches, with fourth instars showing most adaptable feeding behaviors and highest gut protease activities on all diets tested (S1 Fig) . Similar results have been reported from several Lepidoptera where digestion of ingested plant tissues in the gut improves with larval age and is most versatile in actively feeding penultimate instars preceding pupation [34,[67][68][69]. Results from these reciprocal host plant switch experiments also implied that the length of time spent by larvae feeding on a diet was important to identify proteases that participate in rapid adaptation to dietary shifts.…”
Section: Plos Onesupporting
confidence: 79%
“…Numerous studies have demonstrated that phytophagous insects are capable of regulating their digestive physiology to meet nutrient requirements [ 41 , 42 , 43 ]. This is a strategy used by insects to adapt to adverse conditions [ 44 , 45 ]. In the present study, the α-amylase activity in larval midgut was found to be significantly reduced in all AI-treated host plant groups, but the trypsin activity was significantly increased in the AI-treated JM and BP groups.…”
Section: Discussionmentioning
confidence: 99%
“…While the inhibition of trypsin‐like activities is a promising strategy for controlling soybean leaf defoliators (Júnior et al, 2020; Mendonça et al, 2020; Meriño‐Cabrera et al, 2018, 2019, 2020), there is a knowledge gap regarding the potential of this strategy for controlling phytosuccivorous stink bugs. Here, by using computational modelling predictions and biochemical characterisations, we demonstrated the potential of SKTI to inhibit E. heros trypsin.…”
Section: Discussionmentioning
confidence: 99%